ESTUDO DE VALORES DE REFERÊNCIA PARA OS INDICADORES DO PBQP-H VOLTADOS À SUSTENTABILIDADE DE CANTEIROS DE OBRA - Costa, Dayana Bastos; álvares, Juliana Sampaio; Silva, Marcos Brandão; Santos, Vivia Andrade dos (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The interference caused by construction sites activities in the natural environment causes significant impacts on local and global scale. In order to minimize these negative impacts, the knowledge of its causes is indispensable. For this reason, the construction sector has been using sustainability indicators for monitoring site environmental conditions. In this context, in 2012, the Brazilian Habitat Quality and Productivity Program (PBQP-H) incorporated six indicators focused on the construction site sustainability. However, the lack of reference values for these indicators, in order to guide the management of environmental aspects related to water and energy consumption and waste generation on construction sites, is still a limitation to the proper use of them. Therefore, the present work aims to stipulate reference ranges for these PBQP-H indicators, from the development of a database and analysis of the values collected in existing constructions. The study was conducted from three main steps: Sample selection; Data collection and database assembly; and Reference ranges definition. This main study contribution is a better understanding of the construction sites behavior according to the mentioned environmental aspects (related to the PBQP-H indicators), in a way to guide the construction sector in the use of such parameters.